Using impromptu role-playing as an instructional technique to improve senior high school students' speaking skills in EFL context - Ni'matuzzakiyah Ni'matuzzakiyah; Taqiyuddin Taqiyuddin; Fadhila Yonata; Muslena Layla (Pioneer: Journal of Language and Literature, 2026)
Students’ speaking problems include limited vocabulary mastery and insufficient opportunities for classroom practice. Previous studies have shown that impromptu role-play is an effective technique for improving speaking skills. This study aims to investigate the effect of the impromptu role-play technique on the English-speaking ability of eleventh-grade English Literature students at a senior high school in Tanjungpinang. This research employed a pre-experimental one-group pre-test and post-test design. The instrument was a two-minute speaking test performed in front of the class. The sample consisted of 30 students selected through purposive sampling. The data were analyzed using SPSS version 26. The result of the paired-sample t-test revealed a significance value of 0.000, which was lower than 0.05, indicating that the alternative hypothesis was accepted and the null hypothesis was rejected. This finding shows that the implementation of impromptu role-play significantly improved students’ speaking skills. The study implies that impromptu role-play can be used as an effective technique to promote students’ speaking performance and confidence through simulated real-life communication.